2008
DOI: 10.1080/09523980701847131
|View full text |Cite
|
Sign up to set email alerts
|

Social patterns in mobile technology mediated collaboration among members of the professional distance education community

Abstract: The aim of this study was to identify social patterns in mobile technology mediated collaboration among distributed members of the professional distance education community. Ten participants worked for 12 weeks designing a master's programme in information sciences. The participants' mobile technology usage activity and interview data were first analyzed to get an overview of the density and distribution of collaboration at individual and community levels. Second, the results of the social network analyses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…In this case study [56], the participants shared a major problem, which was an assignment to design a new distance education master's program in a new domain (see Fig. 2).…”
Section: Case Study 1: Designing a New Virtual Master's Program In Th...mentioning
confidence: 99%
“…In this case study [56], the participants shared a major problem, which was an assignment to design a new distance education master's program in a new domain (see Fig. 2).…”
Section: Case Study 1: Designing a New Virtual Master's Program In Th...mentioning
confidence: 99%
“…Researches have shown that the overuse of cell phone was associated with increasing features of abnormal behavior patterns, such as staying awake overnight and messaging, and it brought about mental emotional dependency for the users [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…By separating the youngsters from their families and weakening family relationships and interactivities, smartphone has been effective in forming the new identity of young generation (14). In comparison to face-to-face relationships the reduction of security and superficiality of social relationships are considered as consequences of cell phone use (15). Threat to death (16) and depression caused by bullying via cell phone (17) are other subsequences of using cell phone.…”
Section: Introductionmentioning
confidence: 99%